Characterization of the Novel IQGAP1-Adrenergic Receptor Pathway in Lung Cancer - Abdul-Aziz, Omar; Osman, Mahasin; Barudi, Yusuf (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.